Does a hippo go to the doctor? : think about how everyone keeps healthy - Ziefert, Harriet (Think about, 2014)
"Does a Hippo Go to the Doctor? explores and explains why animals in the wild don't go to doctors, that some animals can be cared for by vets--but only people use professional medical services throughout their lifetime."--